2016
DOI: 10.1021/acs.inorgchem.6b02148
|View full text |Cite
|
Sign up to set email alerts
|

A New Approach to Sensitize Antitumor Monofunctional Platinum(II) Complexes via Short Time Photo-Irradiation

Abstract: Sensitizing the antitumor activity of monofunctional Pt complexes is a reliable approach to developing antitumor agents different from the classic Pt-based drugs. Considering the poor intracellular accumulation of monofunctional Pt complexes, in this study, the photosensitizing monofunctional Pt complex Pt-BA was derived from a weak BODIPY (boron-dipyrromethene)-derived photosensitizer BA, with the purpose to improve its antitumor cytotoxicity via enhancing its intracellular accumulation with a short time phot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 31 publications
(25 citation statements)
references
References 44 publications
1
24
0
Order By: Relevance
“…Thep hotoinduced ROS generation of BDPAw as expected to be promoted by the heavy atom effect of the Pt II center in this complex. [9,12] BDPA was synthesized with aKnoevenagel reaction according to our reported procedure (Supporting Information, Scheme S1), [13] and Pt-BDPAwas obtained via reacting BDPAwith K 2 PtCl 4 in methanol with ayield of 23 %. Thecomplex Pt-PDPAwith no photosensitizer was prepared as ac ontrol (Supporting Information, Scheme S1).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Thep hotoinduced ROS generation of BDPAw as expected to be promoted by the heavy atom effect of the Pt II center in this complex. [9,12] BDPA was synthesized with aKnoevenagel reaction according to our reported procedure (Supporting Information, Scheme S1), [13] and Pt-BDPAwas obtained via reacting BDPAwith K 2 PtCl 4 in methanol with ayield of 23 %. Thecomplex Pt-PDPAwith no photosensitizer was prepared as ac ontrol (Supporting Information, Scheme S1).…”
Section: Resultsmentioning
confidence: 99%
“…Although Pt-BDPAw as initially constructed with aP t II chelator bis(pyridin-2-ylmethyl)amine (DPA) to improve the photostability of the photosensitizing Pt complex, Pt-BA( Supporting Information, Scheme S1), its lysosome sequestration is quite different from the poor cell uptake of Pt-BA. [9] Because of its photosensitizing nature,this Scheme 1. Chemical structures of Pt-BDPA and Pt-PDPA, and illustration of the photoactivated lysosomale scape of Pt-BDPA.…”
Section: Introductionmentioning
confidence: 99%
“…On the one hand, the platinum center is able to improve the ROS production ability of PSs due to the heavy atom effect. On the other hand, the photoinduced ROS is able to destroy the cell membranes and promote the cellular uptake of the platinum complexes …”
Section: Figurementioning
confidence: 99%
“…The induced electronic transition can involve several processes depending on nature of the populated excited state(s), such as., internal‐ligand, metal‐centered or metal‐to‐ligand charge‐transfer transitions, which eventually determines the action mechanism (for example, photooxidation, ligand photorelease, changes in the metal oxidation state, photosensitization or non‐radiative decay) . In that framework, a recent work by He, Guo and co‐workers demonstrated that it is possible to use photoactivation as a method to promote cell uptake of a monofunctional platinum drug . Although that work is focused on photoinducing reactive oxygen species to damage the cell membrane rather than disrupting the DNA, it clearly highlights the potential of monofunctional drugs in PACT.…”
Section: Introductionmentioning
confidence: 99%
“…[23] In that framework, ar ecent work by He, Guo and coworkers demonstrated that it is possible to use photoactivation as am ethodt op romote cell uptake of am onofunctional platinum drug. [24] Although that work is focusedo np hotoinducing reactive oxygen speciest od amage the cell membrane rather than disrupting the DNA, it clearly highlights the potential of monofunctional drugs in PACT.…”
Section: Introductionmentioning
confidence: 99%